A politics of priority setting: Ideas, interests and institutions in healthcare resource allocation. (October 2014) - Smith, Neale; Mitton, Craig; Davidson, Alan; Williams, Iestyn
Across a range of health care systems there is a responsibility placed on meso-level budget holders to set priorities and allocate resources within constrained budgets. The literature suggests that these organizations have typically defaulted to historical and/or political processes for decision making. Whilst the literature on resource allocation in health care attests to the political nature of decision making, this has remained largely under-theorized and therefore priority setters may be unfamiliar with the analytic benefits of applying insights from the broader political sciences. Conversely, policy scientists may know relatively little about existing research on how healthcare organizations make allocative and redistributive decisions. This paper aims to open a dialogue between these solitudes by exploring political effects on health care priority setting, using the interpretive concepts ideas, interests and institutions.